Using Laptop At University Level A Survey Based Approach - Muhammad Hafeez (STKIP Rokania Pasir Pangaraian, 2021)
A survey-based research has been conducted to reveal the impacts of using laptops at the university level. For this research BS Mathematics and BS Physics students both morning and evening session of Universities in South Punjab, Pakistan were taken as a population. The population consists of 240 students and 10 teachers of four Universities of South Punjab. The sample of 112 students and10 teachers was taken by Random sampling technique. Questionnaires and interviews were used as a research tool. The results of the study revealed that most of the students used the laptops for study purpose like making assignments on Microsoft word and presentations on the Power Point. The results of teacher’s questionnaires revealed that most of the teachers used laptops for the preparation of lecturer and for different academic activities.